Intelectuais, cultura e pensamento social no Brasil - Totti, Marcelo Augusto (Editora Oficina Universitária, 2021)
Talking about Social Thought in Brazil today has driven researchers to expand the theoretical and methodological limits of sociology in search of a more detailed approach to intellectual and artistic work, cultural militancy and the so-called engaged art. That is, in addition to undertaking analyzes around the "theories of Brazil", research on social thought has turned attention to the different conditions in which these "theories" were read, interpreted and put up for debate, either by intellectuals or by social movements. social to which they were linked.